2006
DOI: 10.1261/rna.249306
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic association and localization of human H/ACA RNP proteins

Abstract: Mammalian H/ACA RNPs are essential for ribosome biogenesis, pre-mRNA splicing, and telomere maintenance. To form mature RNA-protein complexes, one H/ACA RNA associates with four core proteins. In the cell, this process is assisted by at least one nuclear assembly factor, NAF1. Here we report several unanticipated dynamic aspects of H/ACA RNP proteins. First, when overexpressed, NAF1 delocalizes to the cytoplasm. However, its nucleocytoplasmic shuttling properties remain unaffected. These observations demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…Together, the structures of the U65hp/S14 complex and the archaeal H/ACA RNP illustrate how this could occur. The H/ACA RNA is believed to remain stably associated with the snoRNP for multiple rounds of pseudouridylation (24), although a very recent study indicates that only Cbf5 is irreversibly associated with the H/ACA RNA (41).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the structures of the U65hp/S14 complex and the archaeal H/ACA RNP illustrate how this could occur. The H/ACA RNA is believed to remain stably associated with the snoRNP for multiple rounds of pseudouridylation (24), although a very recent study indicates that only Cbf5 is irreversibly associated with the H/ACA RNA (41).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may depend on those of other proteins, such as the multiple nuclear localization signals of NAP57 (Meier and Blobel 1994;Heiss et al 1999;Youssoufian et al 1999). Third, SHQ1 has to act before cotranscriptional association of NAP57 with H/ACA RNA and other core proteins because SHQ1 only binds NAP57 alone and because, once assembled with the core trimer, H/ACA RNAs will no longer exchange (Wang and Meier 2004;Kittur et al 2006). Therefore, SHQ1 may function as a NAP57 chaperone and/or licensing factor marking it ready for RNP assembly.…”
Section: Discussionmentioning
confidence: 99%
“…siRNAs were as previously described ) except for siSHQ1, which was a combination of siSHQ1.1, GCU ACGAAAAUUUGUCAAUTT; siSHQ1.2, GGAAGUAGUUGACG AUGAATT; and siSHQ1.3, GGACAGCAAAACCACUUGUTT (Ambion). Cells were maintained, treated, and transfected as we previously described Kittur et al 2006). Similarly, the inducible H/ACA RNA cell line and related analyses ) and the cell line containing integrated Lac operator arrays (Janicki et al 2004) have been described.…”
Section: Dna/rna Constructs Transfections and Translationsmentioning
confidence: 99%
“…It has recently been shown that overexpressed human Naf1 delocalises to the cytoplasm. 42 This might be due to a concentration effect, shifting the equilibrium between monomeric and dimeric forms of human Naf1. Naf1 most likely assembles along with Cbf5, Nop10 and Nhp2, early during H/ACA snoRNA transcription.…”
Section: Discussionmentioning
confidence: 99%